PELAKSANAAN METODE TASBIH UNTUK MENINGKATKAN KEMAMPUAN MEMBACA AL QURAN - Rizki Alfajri Zein; Reffa Muhammad Adedyo; Syarnubi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
The Tasbih Method emphasizes structured repetition and consistency in recitation practice, similar to the use of tasbih in dhikr. This research uses a qualitative method with a literature study approach and interviews to examine theories, concepts, and research results related to the Tasbih Method. Ustadz Rahman explained that the book